(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2024)
The objective of this article is to analyze the adoption of a systemic conception among school-aged youth to promote environmental responsibility. It draws on a review of studies and research that have addressed environmental education. Within the school context, the definition of the environment has gradually evolved toward a systemic vision in which humans are recognized as active agents, whose actions have consequences on various factors and elements that make up the environment. Likewise, environmental awareness and the commitment assumed progressively contribute to sustainable development.